أثر نظم المعلومات المحاسبية المحوسبة على جودة التقارير المالية: دراسة ميدانية : عينة من البنوك العاملة بمدينة سنار - د. ناهد عوض علي (White Nile Journal for Studies and Research, 2022)
The problem of the study was represented in the weak interest of banks in switching from traditional information systems to computerized systems. The study aimed to identify computerized accounting information systems and clarify the impact of these systems on the relevance and reliability of financial reports. The study hypothesized that there is a relationship between the use of computerized accounting information systems and the reliability of financial reports, and the use of systems Computerized accounting information and the appropriateness of financial reports. The study reached several results, including: Computerized accounting information systems work to provide information in a timely manner, and computerized accounting information systems help in evaluating previous and current financial events. The study recommended the need to search for modern systems used in accounting operations and how to prepare reports, and the continuous development of the system. Accounting information through the use of electronic applications and programs. Keywords: accounting information systems, quality of financial reports